Analisis Hukum Ekonomi Syariah Dalam Transaksi Paylater Pada Aplikasi Shopee - Wati, Ai; Ningsih, Sri Hayati (Jurnal Hukum Ekonomi Syariah, 2023)
Shopee PayLater is Shopee's newest payment method that is easily accessible on smartphones via the internet by Shopee users. The Shopee PayLater payment method offers to active Shopee users. It aims to provide convenience for buyers in the form of loans with low interest rates. However, even though Shopee claims to buy now pay next month without interest, in fact there are still installment fees that users must pay. Shopee also penalizes fines for late payments after maturity. The formulation of the problem in this study includes, how is the mechanism for buying and selling using the PayLater method on the Shopee application? and How is the review of sharia economic law on buying and selling using the PayLater method on the Shopee application? So this study aims to determine the mechanism of buying and selling transactions using PayLater in the Shopee application and to find out the review of sharia economic law on PayLater transactions in the Shopee application. This research is included in the type of qualitative research with data collection techniques used, namely interviews, observation, and documentation. From this data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it was found that in the Shopee PayLater payment method, usury was indicated because from the beginning of the agreement, Shopee set installment interest and penalties to compensate for late payments.  Keywords : Sharia Economic Law, Transaction, PayLater, Shopee